Essays on social norms and status of women in northeastern India - Pal, Sumantra (2020)
Conventional wisdom suggests patriarchal social norms hinder the well-being and empowerment of women in the process of development. I investigate the link between social norms that define women’s status in society and spousal violence. The empirical setting is India’s Northeast, where there is substantial variation regarding patriarchal versus matriarchal customs. In my econometric analysis, I combine in- formation on ancestral social norms from a comprehensive ethnographic atlas with individual-level survey data on spousal violence. Consistent with the established economic theories, the more female-empowering variants of the persistent antediluvian social norms, such as easier divorce regime, non-residence with husband’s kin, and matrilineal descent improve women’s reservation utility and bargaining power within the extant marriages and curtail spousal violence and its acceptance. Ancestral female productive roles enhance women’s value in society and reduce spousal violence. I uncover a complete mechanism of gender disparity from fertility to morality using a novel cross-sectional dataset of 22,000 mothers and their 51,000 children from 92 aboriginal ethnic groups that combine ethnographic and environmental data to demographic data in the northeastern zone of India. Descendants from the ethnic groups with pro-women features tend to discriminate less against their daughters. In ethnic groups which value women more, a typical female child is more likely to be the last born, more likely to experience longer succeeding birth interval, more likely to be breastfed longer, and more likely to receive overall better nourishment. Contemporary female employment status does not drive these effects. Both the magnitude and statistical significance of the effects remain unaltered in regressions with contemporary female employment status. This is because the effects originate from the deep-rooted ancestral female productive roles and pro-women social norms.
Keywords: Hochschulschrift